EP089/#784 Low use of hormone therapy in women with early menopause arising from treatment for cervical cancer. (4th December 2022) - Sousa-Lima, Renata; Machado, Isabella; Freitas, Luiz-Francisco; Veloso, Gilson; Rodrigues, Angelica
Abstract : Objectives: Many cervical cancer patients are premenopausal at diagnosis, and the treatment induces early menopause. The aim of this study was to evaluate the frequency of hormone replacement therapy (HRT) in patients with iatrogenic menopause due to cervical cancer treatment and the impact on clinical and social outcomes on the quality of life. Methods: Observational, retrospective cohort study, carried out in public health Brazilian institutions, from February to December 2021. Women aged 18 to 50 years, diagnosed with menopause initiated after treatment were selected and interviewed. Results: One hundred and thirty patients were included. Only 33% of them had been advised about menopause symptoms, 23% about HRT, and only 20% received hormone replacement. Data analysis, using Fisher's or Pearson's chi square test, has shown that earlier age and higher education were associated with a greater probability of receiving HRT (p=0.021 and 0.001, respectively). Other important data were the return to work after treatment, from a social point of view and the lack of information about bone health. Conclusions: A small percentage of cervical cancer survivors have adequate information about menopause and HRT, and a smaller proportion receive hormone replacement therapy. These data show the need for attention to these young women who have menopause arising from treatment, and reinforce the importance for survivorship guidelines for cervical cancer patients.